2022 IEEE 13th International Green and Sustainable Computing Conference (IGSC) 2022
DOI: 10.1109/igsc55832.2022.9969370
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Automatic Gym Workouts Recognition Locally on Wearable Resource-Constrained Devices

Abstract: Automatic gym activity recognition on energyand resource-constrained wearable devices removes the humaninteraction requirement during intense gym sessions -like softtouch tapping and swiping. This work presents a tiny and highly accurate residual convolutional neural network that runs in milliwatt microcontrollers for automatic workouts classification. We evaluated the inference performance of the deep model with quantization on three resource-constrained devices: two microcontrollers with ARM-Cortex M4 and M7… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Fig. 1(a) shows the employed model, which is a residual network consisting of 10 1D-convolutional layers and 1 fully connected (dense) layer [37]. The whole network can be divided into two parts: the backbone and the classifier.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fig. 1(a) shows the employed model, which is a residual network consisting of 10 1D-convolutional layers and 1 fully connected (dense) layer [37]. The whole network can be divided into two parts: the backbone and the classifier.…”
Section: Methodsmentioning
confidence: 99%
“…A detailed description of the data set can be found in [66], in which the authors deployed a Resnet neural network for workout recognition and achieved an accuracy of 91%. The authors also tried a real-time edge evaluation with the compressed network in [37] and reported an accuracy of 88%.…”
Section: A Recgym: Gym Activity Recognitionmentioning
confidence: 99%
See 2 more Smart Citations